The Relationship Between Agricultural Value Added, Investment and Consumption: Vector Error Correction Model Approach - Sasongko, Budi; Puspaningtyas, Meinarti; Bawono, Suryaning (AIBPM Publisher, 2022)
The purpose of this study was to determine the impact of the relationship between agriculture on investment and consumption in Indonesia. This study uses data from a period of 36 years, from 1985 to 2020 by vector modeling to understand causal relationships between variables. This research is based on secondary data from the world bank. We use the variables of value-added agriculture, consumption, and investment in Indonesia. We find that macroeconomic variables such as agricultural value-added, consumption to GDP, and non-financial investment have a mutually influencing relationship. Changes that occur in one variable will affect other variables. With the decline in the value-added of agriculture, the level of consumption of the total GDP in Indonesia will increase. This happens because in Indonesia the decline in agricultural value-added can make consumption increase due to imports of agricultural products which increase along with it. However, an increase in consumption will also increase the value-added of agriculture, an increase in investment in the non-financial sector will increase the value-added of agriculture, and an increase in investment will increase consumption.